2021
DOI: 10.2196/29965
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Nerve Noninvasive Neuromodulation in Adults With Neurological Conditions: Protocol for a Scoping Review

Abstract: Background Cranial nerve noninvasive neuromodulation (CN-NINM) via translingual nerve stimulation (TLNS) is a promising new intervention combined with neurological rehabilitation to improve outcomes for persons with neurological conditions. A portable neuromodulation stimulation (PoNS) device rests on the tongue and stimulates cranial nerves V and VII (trigeminal and facial nerves, respectively). Emerging evidence suggests that CN-NINM using the PoNS device, combined with targeted physical therapy,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In individuals with mild-to-moderate traumatic brain injury, balance was shown to be both improved and sustained after treatment [TBI; (Tyler et al, 2019;Ptito et al, 2021)]. Recent work in individuals with Multiple Sclerosis [MS; (Tyler et al, 2014)], or stroke has demonstrated the potential for TLNS/PT rehabilitation that spans multiple clinical populations (Danilov et al, 2007;Galea et al, 2017;Leonard et al, 2017;Boughen et al, 2022). Further, within the growing real world clinical experiences, incidental observations of cognitive and mental health improvements have often been reported by clinicians and patients alike (Frehlick et al, 2019;Smith et al, 2020).…”
mentioning
confidence: 99%
“…In individuals with mild-to-moderate traumatic brain injury, balance was shown to be both improved and sustained after treatment [TBI; (Tyler et al, 2019;Ptito et al, 2021)]. Recent work in individuals with Multiple Sclerosis [MS; (Tyler et al, 2014)], or stroke has demonstrated the potential for TLNS/PT rehabilitation that spans multiple clinical populations (Danilov et al, 2007;Galea et al, 2017;Leonard et al, 2017;Boughen et al, 2022). Further, within the growing real world clinical experiences, incidental observations of cognitive and mental health improvements have often been reported by clinicians and patients alike (Frehlick et al, 2019;Smith et al, 2020).…”
mentioning
confidence: 99%